2009
DOI: 10.1038/ja.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase total synthesis of the chitinase inhibitor Argadin using a supported acetal resin

Abstract: A versatile solid-phase total synthesis was applied to the rapid preparation of Argadin, a natural product isolated and characterized as a cyclopentapeptide by our group, which possesses superior inhibitory activity against family-18 chitinases. The synthetic strategy includes peptide synthesis by using an Fmoc (9-fluorenylmethoxycarbonyl) protective group, macrolactamization, acetylguanylation and formation of hemiaminal accompanied by total deprotection, including cleavage from resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Syn-trizole 110 (Figure ) displayed high inhibitory activity against SmChiB (IC 50 value of 0.022 μM), which is approximately 30-fold stronger than that of the precursor (approximately 300-fold potency as compared to natural product precursor). Syn–anti selection for the in situ screening by LCMS-SIR revealed that a combination of azide and alkyne had led to the accelerated formation of syn-trizole in the presence of pure (His) 6-SmChiB in an enzyme-dose-dependent manner, thereby validating syn-50 as an in situ “hit” and confirming that its formation required the enzyme active site to be accessible. , …”
Section: In Situ Click Chemistrymentioning
confidence: 86%
See 1 more Smart Citation
“…Syn-trizole 110 (Figure ) displayed high inhibitory activity against SmChiB (IC 50 value of 0.022 μM), which is approximately 30-fold stronger than that of the precursor (approximately 300-fold potency as compared to natural product precursor). Syn–anti selection for the in situ screening by LCMS-SIR revealed that a combination of azide and alkyne had led to the accelerated formation of syn-trizole in the presence of pure (His) 6-SmChiB in an enzyme-dose-dependent manner, thereby validating syn-50 as an in situ “hit” and confirming that its formation required the enzyme active site to be accessible. , …”
Section: In Situ Click Chemistrymentioning
confidence: 86%
“…Syn−anti selection for the in situ screening by LCMS-SIR revealed that a combination of azide and alkyne had led to the accelerated formation of syn-trizole in the presence of pure (His) 6-SmChiB in an enzyme-dose-dependent manner, thereby validating syn-50 as an in situ "hit" and confirming that its formation required the enzyme active site to be accessible. 137,138 4.8. Carbonic Anhydrase Inhibitors Carbonic anhydrases (CA) are a family of metalloenzymes that catalyze the interconversion of HCO 3 − and CO 2 .…”
Section: Chitinase Inhibitorsmentioning
confidence: 99%
“…173 A solid-phase total synthesis of argadin has also been recently accomplished using a supported acetal resin. 174 The mannopeptimycins b 193, a 194, g 195, d 196, and 3 197 are a group of cyclic glycopeptides originally isolated from the LL-AC-98 strain of Streptomyces hygroscopicus. They showed significant activity against a wide range of Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecium.…”
Section: Alkaloids From Microorganismsmentioning
confidence: 99%